Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T15:25:17+01:00
A) 1/3x - 2= x+2

1/3x - x = 2 + 2
-2/3x = 4 / * (-3/2)
x = -6

b) 1-6/7x=4/7

- 6/7x = 4/7 - 1
- 6/7x = -3/7 / * ( -7/6)
x = 1/2

c) 6(1/4x-2) = 18

3/2x - 12 = 18
3/2x = 18 + 12
3/2x = 30 / * 2/3
x = 20

d)x/6-1/6=1

x/6 = 1 + 1/6
1/6x = 1 + 1/6 / * 6
x = 6 ( 1 + 1/6 )
x = 6 + 1
x = 7

e)-2(2x-1) = x/3

-4x + 2 = 1/3x
-4x + 1/3x = -2
-3 i 2/3x = -2
-11/3x = -2 / * ( - 3/11 )
x = 6/11

f) 2/5 (3-x) = -2

6/5 - 2/5x = -2
-2/5x = -2 - 6/5
-2/5x = -3 i 1/5
-2/5x = - 16/5 / * ( - 5/2 )
x = 8

g)3/4(2-3x) = -6

3/2 - 9/4x = -6
-9/4x = -6 - 3/2
-9/4x = -7 i 1/2
-9/4x = -15/2 / * ( - 4/9 )
x = 10/3

h)1/5(x-3) = 9-x

1/5x - 3/5 = 9 - x
1/5x + x = 9 + 3/5
6/5x = 9 i 3/5
6/5x = 48/5 / * 5/6
x = 8

pozdrawiam :)
2010-03-08T15:29:40+01:00
Całość daję w załączniku :))